2011
DOI: 10.1557/opl.2011.1272
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of CdMnTe Detector Performance by MnTe Purification

Abstract: Residual impurities in manganese (Mn) are a big obstacle to obtaining high-performance CdMnTe (CMT) X-ray and gamma-ray detectors. Generally, the zone-refining method is an effective way to improve the material's purity. In this work, we purified the MnTe compounds combining the zone-refining method with molten Te, which has a very high solubility for most impurities. We confirmed the improved purity of the material by glow-discharge mass spectrometry (GDMS). We also found that CMT crystals from a multiply-ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In Figure 3(a), the DOCP was zero at  = 18. Furthermore, Figure 3(b) shows the Mn ions concentration on the sample surface, which was obtained by the PL peak photon energies at 300 K using the following equation [19] g ( ) = 1.528 + 1.316 [eV]. (3)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 3(a), the DOCP was zero at  = 18. Furthermore, Figure 3(b) shows the Mn ions concentration on the sample surface, which was obtained by the PL peak photon energies at 300 K using the following equation [19] g ( ) = 1.528 + 1.316 [eV]. (3)…”
Section: Resultsmentioning
confidence: 99%
“…This redshift is resulted from a change in the bandgap energy. The bandgap energy was reported as a function of the Mn ion concentration x and the temperature T[19], for the range…”
mentioning
confidence: 99%
“…Therefore, we chose stable MnTe compounds as starting material for purification. Details on purifying the material were described earlier [4]. We found that the performance of a CMT detector grown with two-times purified MnTe with Te solvent was improved.…”
Section: B Materials Purificationmentioning
confidence: 91%